(untitled) (Research, Society and Development, 2020)
Assess the relationship among quality of life (QoL) domains with age, gender, level of physical activity and nutritional status of institutionalized elderly. This is a quantitative, cross-sectional study with 245 elderly of both sexes, living in public and private Long-Stay Institutions for the Elderly (LSIEs). The International Physical Activity Questionnaire, short version, World Health Organization Quality of Life - bref Instrument and a structured questionnaire contemplating gender and age were used. Weight and height measurement were also measured to determine body mass index (BMI) and classify nutritional status according to the Pan American Health Organization (2002). Results at a maximum significance level of 5% (p0.05) were considered significant. The highest mean of QoL was observed in the environmental, 32.0 (±11.9) and the lowest in the social, 24.3 (±11.9). The elderly aged 60-69 years presented lower average in the social domain (p=0.41) in relation to the other age groups, the psychic and social domains presented significantly higher means among sedentary elderly (p≤0.01). The correlation between the environmental domain and BMI was significantly inverse (r=-0.128, p=0.045) and residents in public LSIEs presented higher averages in all domains (p≤0.05) when compared the Institutions. It was concluded that the elderly QoL perception was better in the environmental domain and worse in the social domain. The younger elderly had lower scores in the social domain, the sedentary had the best scores in the psychic and social domains, the obese had lower score in the environmental domain and the residents of public LSIEs had the best score in all domains.